Pengaruh berbagai campuran ransum komersial, jagung kuning dan dedak padi fermentasi dengan kadar protein yang berbeda terhadap penampilan ayam Broiler fase finisher - H Herlinae; Y Yemima; Transiana Aristayani (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2020)
This study aims to determine the effect of various mixtures of commercial rations, yellow corn and fermented rice bran with different protein content on the appearance of finisher phase broiler chickens. This research was conducted using a Completely Randomized Design (CRD) with A treatment of 20% protein level (86.89% BR-1, 8.74% yellow corn, 4.37% fermented rice bran) B treatment of 19% protein level (78.15% BR-1, 14.57% yellow corn, 7.28% fermented rice bran) C treatment 18% protein level (61.41% BR-1, 20.39% yellow corn, 10.20% rice bran fermentation) treatment D 17% protein level (60.66% BR-1, 26.23% yellow corn, 13.11% fermented rice bran) each treatment was repeated 5 times so that there were 20 experimental units. The parameters observed were body weight gain, feed consumption, feed conversion and final body weight. The results showed the administration of a mixture of commercial rations, yellow corn and fermented rice bran significantly affected the body weight gain of broiler chickens week 4 and week 5, feed conversion to week 4 and final body weight. Significantly influences body weight gain at week 6 and conversion of week 5 rations. No effect on consumption at week 4, week 5, week 6 and feed conversion at week 6. Keywords : Broiler chicken, fermented rice bran, yellow corn,and protein.